Eco-friendly evaluation of rifaximin in tablets by capillary electrophoresis - Kogawa, Ana Carolina [UNESP]; Van Schepdael, Ann; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2019)
Rifaximin, an oral antimicrobial, has no standardized analytical methods in many official compendia. In this context, the aim was to develop and validate an analytical method by capillary electrophoresis for quantification of rifaximin in tablets. The choice of capillary electrophoresis was based on the concepts of green analytical chemistry, taking into account the health of the operator and environment, analytical conscience, as well as the parameters of linearity, selectivity, precision, accuracy and robustness. The method was linear between 50 and 500 μg mL-1 (r = 0.9993) using purified water and ethanol in the sample preparation, silica capillary, borate buffer 25 mM pH 9.5, 20 kV and 290 nm. It presented good precision intraday (1.30%) and interday (1.56%). The accuracy complied with average recovery of 100.24%, as well as selectivity in the presence of impurities and degradation products and robustness against variations in the concentration, pH, rinse time of the buffer, voltage, wavelength, injection time and temperature. The capillary electrophoresis method developed for the evaluation of rifaximin tablets is low cost, fast, miniaturized, clean and environmentally friendly and can be used by laboratories and chemical and pharmaceutical industries for quality control of the drug.